Chemical profiling and antimicrobial potential of crude extract and essential oil from Conyza bonariensis leaves - Fulgence Ntangere Mpenda; Simeon P. Nsindagi; Cyprian B Mpinda (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Microbial infections have made significant contributions to the global health burden, particularly in developing countries with lagging economies. Challenges arising from the evolution of antimicrobial-resistant (AMR) bacteria have led to the search for novel antimicrobial agents, especially those derived from medicinal plants. Therefore, this study aimed to assess the antibacterial activity of ethyl acetate crude extracts and essential oils from C. bonariensis collected from the Mbeya region of Tanzania. Initial experimental activities involved the preparation of crude extracts and essential oil, which were then tested for antimicrobial activity against selected test organisms (Staphlococcus aureus (ATCC29213), Bacillus subtilis (ATCC6051), Escherichia coli (ATCC8736), Salmonella typhi (ATCC6539), and Candida albicans (DSM1665)) by using the disc diffusion method. On the other hand, the chemical composition profiling of ethyl acetate and essential oils was performed by gas chromatography mass spectrometry (GC-MS). The crude extracts and essential oil of C. bonariensis leaves from Tanzania were demonstrated antibacterial and antifungal activity. The minimum inhibitory concentration (MIC) of leaves' ethyl acetate crude extract was 25 mg/mL > MIC > 12.5 mg/mL for tested organisms, with the exception of C. albicans, where the MIC was 50 mg/mL > MIC > 25 mg/mL. Similarly, for all tested organisms, the MIC of leaves essential oils was :1 > MIC > l:2, except S. typhi, where the MIC was 2:1 > MIC > 1:1. On the other hand, 2,4-di-tert-butyl phenol in crude leaf extracts had the highest percentage composition of peak area (41%); whereas, in essential of, 2,4-Di-tert-butyl phenol had the highest percentage composition (38.8%). The present findings have demonstrated the antimicrobial potential of ethyl acetate crude extract and essential oil of C. bonariensis leaves from Tanzania and validate the wide use of the plant by local communities, particularly the local community of Mbeya region in Tanzania.